2002
DOI: 10.1002/cncr.10614
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided fine-needle aspiration in 179 cases

Abstract: BACKGROUND Recently, endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) has emerged as a diagnostic adjunct for small pancreatic lesions and abdominal and mediastinal lymph node diseases. DESIGN. During a 21‐month period, we performed 179 EUS‐FNAs in 166 consecutive patients; these data are the subject of this study. An average of 2.6 needle passes were obtained and aspiration was performed most commonly in the pancreas (162 cases, 91%). The FNA smears were reviewed using six diagnostic categories (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 13 publications
10
113
1
1
Order By: Relevance
“…[113][114][115][116][117][118][119] Even minute lesions of 5 mm can be visualized and biopsied. Contrary to what might be expected, the size of the lesions, whether small ( 25 mm) or large (>25 mm) does not influence the overall diagnostic yield, sensitivity, specificity, or accuracy of the method.…”
Section: Eus-fnamentioning
confidence: 99%
“…[113][114][115][116][117][118][119] Even minute lesions of 5 mm can be visualized and biopsied. Contrary to what might be expected, the size of the lesions, whether small ( 25 mm) or large (>25 mm) does not influence the overall diagnostic yield, sensitivity, specificity, or accuracy of the method.…”
Section: Eus-fnamentioning
confidence: 99%
“…Endoscopic ultrasound-guided FNA (EUS-FNA) is believed to provide cytological diagnosis with specificity of around 100%. 24,60,62 Therefore, usage of EUS-FNA whenever necessary can achieve early diagnosis and can act as a sound basis for prompt treatment and definitive management of pancreatic cancer, including PD. Other factor that is regarded highly in terms of survival outcome is tumor resection margin.…”
Section: Discussionmentioning
confidence: 99%
“…In a relatively large prospective trial evaluating the use of EUS, Anderson et al found a sensitivity of 93% in detecting pancreatic tumors with a mean tumor diameter of 1.51 cm [13]. Furthermore, EUS has showed the added utility of allowing fine needle aspiration to distinguish visualized masses further aiding in diagnosis, staging, and in determining a management strategy [14,15].…”
Section: Diagnosismentioning
confidence: 99%